Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Volume-V General Areas Education Government of Assam - Planning Commission (Planning Commission, 1985)
More than 70% of the school buildings in the State are below the normal standard. For motivation and retention of children the school buildings must be brought atleast to the minimum standard. Schools are also to be equipped with necessary furniture and teaching learning materials with an attractive compound, the Pre- Primary/Pre-school/Early childhood Education which is a most important pre-requisite to Primary Education must be improved to the minimum standard with equipment, furniture etc.
Government of Assam, Planning and Development Department